(untitled) (Dhaka University Journal of Biological Sciences, 2025)
This study evaluated the effects of micronutrients (B, Fe and Zn) on the vegetative growth and shoot nutrients (K, Ca, Fe and Zn) status of chickpea (Cicer arietinum L.) grown under different moisture regimes (50%, Well-Watered; 25%, Mild-Stressed and 12.5%, Severe-Stressed) in greenhouse condition. Micronutrients were supplied alone and in combination as foliar spray to plants with severe-stressed condition. Results showed a significant decline in shoot height (p < 0.0001), fresh weight (p < 0.0001), dry weight (p < 0.0001) and relative water content (p = 0.0001) from well-watered to severe-stressed condition, although no remarkable change was observed after the application of micronutrients. Significant reduction in root fresh weight (p= <0.0001) and dry weight (p = 0.0071) was also seen in severe-stressed condition compared to that in the well-watered condition. Micronutrients were found to stimulate growth of root dry weight and root length under severe-drought condition. Significant increase of leaf area (p = <0.0001) and decrease of leaf chlorophyll content (p = <0.0001) were noted under severe-drought condition compared to that of well-watered condition. Concentrations of K, Ca, Zn and Fe increased in plant shoot tissue after the application of micronutrients although depending on the combination of treatments. Results thus indicated a promising role of micronutrient use in the amelioration of drought stress for the cultivation of chickpea. Dhaka Univ. J. Biol. Sci. 34(1): 97-107, 2025 (January)